Keanekaragaman Jenis Tanaman Biofarmaka di Objek Wisata Kesehatan Jamu Kalibakung Tegal sebagai Implementasi E-book Pada Pembelajaran Biologi - Salsabila Zahirotul Maghfiroh; Fibria Kaswinarni; Rivvana Citraning Rahayu (Florea : Jurnal Biologi dan Pembelajarannya, 2022)
The diversity of Biopharmaca plant species in the Kalibakung Jamu Health Tourism area has not been fully utilized by the surrounding community, the community is only familiar with a few plants which makes this one of the factors not utilizing plants in Kalibakung Jamu Health Tourism. The purpose of this study was to determine the diversity of Biopharmaca plant species in Kalibakung Jamu Health Tourism. The research method used is quantitative and qualitative methods. Observations were made using the plot method with each plot measuring 15x15 meters for tree vegetation, 10x10 meters for shrub vegetation and 2x2 meters for herbaceous vegetation. Data were analyzed using the Shannon Wiener Diversity Index (H') and the potential of Biopharmaceutical plants was analyzed qualitatively. From the results of the study it was known that the types of vegetation found in the area were trees, shrubs and shrubs with an H level for tree vegetation of 1.530, shrub vegetation 0.625 and shrub vegetation 1.745.